1991
DOI: 10.1111/j.1365-2958.1991.tb01820.x
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of genetic competence in Bacillus subtilis

Abstract: Genetic competence develops as a global response of Bacillus subtilis to the onset of stationary phase, in glucose-minimal salts-based media. The onset of competence is accompanied by the expression of several late gene products that are required for the binding, processing and uptake of transforming DNA. A number of regulatory genes have been identified that are needed for the appropriate synthesis of the late gene products. The regulatory gene products include a number of known transcription factors, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…DNA transport is probably the Ca2+-In Bacillus subtilis it is proposed that competence is requiring step at the expression stage (Lacks & Green-induced in response to a variety of signals including berg, 1973;Set0 & Tomasz, 1974Lacks, 1977; growth stage and nutritional information (for a review, ClavC et al, ClavC & Trombe, 1989). Addition of see Dubnau, 1991). Culture-medium titrations showed C F to the medium did not change the Ca2+ dependence no variation in glucose and phosphate concentrations (Fig.…”
Section: Cf Activation Of Competence and Culture Lysismentioning
confidence: 99%
“…DNA transport is probably the Ca2+-In Bacillus subtilis it is proposed that competence is requiring step at the expression stage (Lacks & Green-induced in response to a variety of signals including berg, 1973;Set0 & Tomasz, 1974Lacks, 1977; growth stage and nutritional information (for a review, ClavC et al, ClavC & Trombe, 1989). Addition of see Dubnau, 1991). Culture-medium titrations showed C F to the medium did not change the Ca2+ dependence no variation in glucose and phosphate concentrations (Fig.…”
Section: Cf Activation Of Competence and Culture Lysismentioning
confidence: 99%
“…The AbrB protein acts as repressor during vegetative growth to prevent expression of stationary-phase-specific genes, including aprE, which encodes the major secreted alkaline protease known as subtilisin. However, AbrB can also activate gene transcription, for example of hpr and competence genes (Dubnau, 1991 ;Perego & Hoch, 1988). The sinI-sinR operon also contributes to the regulation of late-growth development in B. subtilis (Smith, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether any of the gene products known to alter gene expression during stationary growth phase also regulate hut expression, histidase expression was examined in strains containing mutations in the comA (9), comP (9), degUS (30), sin (28,32), pai (16), hpr (32), sigH (28), spoOA (28), spoOB (28) the autoradiogram showed that the relative levels of hutP RNA were 1 in T0.85 cells (Fig. 2, lane 1 Regulation ofhut expression by catabolite repression during stationary growth phase.…”
Section: Methodsmentioning
confidence: 99%